Factors related to delayed treatment: A case report of a huge cutaneous horn and review of the literature. (December 2020) - Starnoni, Marta; De Santis, Giorgio; Lolli, Francesca; Pinelli, Massimo
Abstract: We present a case of a man with a giant cutaneous horn over his frontal region. This case has been presented for the size of the lesion, due to delayed treatment, and to illustrate the reasons why the growth of this lesion has been possible in a western country, in the 21st century. It was a solitary, not painful lesion which caused significant aesthetic problems. The diagnosis was based on an ultrasonographic study and the treatment of choice was a surgical excision. This case is an opportunity to review the literature about the cutaneous horns, to talk about the main causes of delayed diagnosis and treatment of cutaneous lesions and, to define the role of the specialist in the assessment of emotions and patient support. Highlights: The diagnosis of cutaneous horn is clinical, based on the lesion's morphology. The reasons of a such important skin lump growth in a developed country can be influenced by sociodemographic variables. The risk significantly increases in people who are living alone, in 1rural areas, and with a different culture. Psychological factors may also play a role in patient's delay. A high level of fear can minimize the seriousness of symptoms.